Development of Malaysian Driver Anger Scale (MDAS) : a pilot survey and reliability analysis - Naida Rosli,; Kamarudin Ambak,; Sharifah Osman@Liew Shyuan Yei,; Putranto, Leksmono Suryo (Penerbit Universiti Kebangsaan Malaysia, 2021)
Anger is a negative emotion and able to present problems on the road because it can cause aggressive driving, violation and can lead to risk of road accidents. Malaysia is one of the countries that records highest number of accident due to aggressive driving. Therefore, this study has proposed Malaysian Driver Anger Scale (MDAS) which is suitable in the context of driving culture in Malaysia by modifying instrument driving questionnaire anger scale (DAS) introduced by Deffenbacher et al. (1994). This study identified research gaps of Driving Anger Scale (DAS) by doing a literature review. Initially, this study attempted to find a suitable primary theory model to describe anger among drivers. After DAS was selected as a reference theory model, this study tried to find out DAS study applied in Malaysia in order to figure out how well this theory model used in Malaysia. Then, based on previous studies, this study drafted a questionnaire and proposed MDAS. Pilot test was run to identify the weaknesses of items in the set of the survey form and to determine the reliability internal consistency of items. A Questionnaire form was selected as an instrument and scoring were based on a 5 point Likert scale. This study was conducted among drivers in Parit Raja, Batu Pahat Johor. A 30 voluntary respondents were selected to answer the survey form. They were approached face to face to determine the weaknesses of items in the set of the survey and all the weaknesses or errors in the survey form were recorded for improvement. All data collected were analyzed using Statistical Package of Social Science (SPSS) to gain Cronbach’s Alpha coefficient. The pilot test result analysis showed Cronbach’s alpha coefficient for DAS (Discourtesy α = .922; Traffic Obstruction α =. 902; Hostiles Gestures α = .896; Slowly Driving α = .838; Police Presence α = .927; Illegal Driving α = .906) and Road Accident Risk Factor (α = .776) is acceptable. Only the Psychological Effect (α = .576) showed less satisfactory Cronbach’s alpha coefficients. Therefore, this study will modify all the items with less satisfactory results in addition to seeking advice from the expert.. This study will proceed with future work by interviewing respondents who have experiences related to road bullying to gather more information on anger driving in Malaysia.